Application of Chitosan as Antibacterial for Pangasius Fillet at Low Temperature Storage - Windi Damayanti; Emma Rochima; Zahidah Hasan (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
AbstractThis research were to obtain the optimal concentration of chitosan as an antibacterial material wich had the longest of storage period of pangasius fillet at low temperature storage (5-10oC). The method used is an experimental method with a completely randomized design, four treatments and three replications. Pangasius fillet was soaked with chitosan 0%, 1%, 2% and 3% for 3 minutes, then packed with styrofoam and plastic wrap and stored at low teperature. The observation were made on day 1st, 3rd, 5th, 6th ,7th, 9th,10th, 11th and 12th. The parameters observed total bacterial colonies, the degree of acidity (pH), weight loss, and antibacterial activity of chitosan using disc diffusion methods. The conclusion of research was that the 2% chitosan is optimal concentration for pangasius fillet storage at a low temperature until day 11th, with a total 6.7 X105 cfu/g of bacterial colonies, pH 6.67 and total 6,78 % of weight loss.Chitosan also has a higher antibacterial capability against Escherichia coli (Gram negative bacteria) than Staphylococcus aureus and Bacillus subtilis (Gram positive bacteria).